Perceptions of Church Financial Transparency: Ethical-Theological Analysis and Financial Accountability - Rossalina Christanti; Wahju Satria Wibowo; Yahya Wijaya (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2023)
This paper examines the perception of transparency among the Church Councils with an ethical-theological analysis and an analysis of financial accountability. The background of the problem is that there are different perceptions among the congregations regarding church financial accountability. These differences reflect differences in theological ethical content. The data collection method used is a mix-method, which uses quantitative tools by distributing questionnaires and in-depth interviews with several church assemblies. The final number of respondents is 167 church assemblies from two church groups, namely the Indonesian Christian Church of the Central Java Regional Synod (Gereja Kristen Indonesia Sinode Wilayah Jateng/GKI SW Jateng) Region of Solo and the Javanese Christian Churches (Gereja-gereja Kristen Jawa/GKJ) Region of North Yogyakarta. The result is a moral obligation is proven to have a significant effect on transparency and intention to disclose financial information to the congregation. This moral obligation to make church finances transparent is based on the church community or congregation members. The ethical drive mainly comes from the community. Theologically, this result on the one hand confirms the existence of the church as a community of faith that drives the formation of values. On the other hand, it presents an opportunity for the church to make a program that formed a personal value of transparency in the Church Council. The research contribution is to the development of the Church Council's guidance on financial accountability and the development of theological ethical values.